Digital Marketing Strategies of Kaloris Herbal Beverage MSMEs in Expanding the Local Market - Utomo, Asep Purwo Yudi; Nugraini, Siti Hadiati; Feriady, Muhammad; Fidaroeni, Hanum Sa’ada; Utami, Salsabila Budi (Universitas Negeri Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as a cornerstone of the national economy, yet they continue to face significant challenges in terms of promotion and digital transformation. Kaloris Herbal Beverage MSME, as a producer of natural-based products, holds substantial potential in line with the growing trend of healthy lifestyles. However, its marketing practices remain largely conventional, relying primarily on word-of-mouth promotion. The major obstacles encountered include weak branding efforts, limited digital content management, and underutilization of social media and online marketplaces. To address these issues, this community engagement program applied a Participatory Action Research (PAR) approach, emphasizing training in digital marketing strategies such as social media optimization, visual content creation, and marketplace management. The outcomes demonstrate that Kaloris MSME successfully established a more consistent digital identity, reflected in a significant increase in social media followers, engagement rates, and local consumer orders. This surge in digital interaction was also accompanied by positive consumer responses regarding product quality and packaging. Thus, strengthening digital marketing strategies has proven effective in expanding local market reach, enhancing brand awareness, and improving the competitiveness of herbal beverage MSMEs in the digital economy era.